Sustainable Consumption Practices Among Civil Servants In Perak And Kedah, Malaysia - Zakaria, Siti Marziah (2008)
Human are generally responsible for the destruction of environment in Malaysia and throughout the world through their production and consumption activities. The main objective of this study was to analyze sustainable consumption practices among civil servants. The study assessed the adoption of value towards environment, attitude towards sustainable consumption practices, materialistic value orientation, and sustainable consumption practices. The factors influencing civil servants’ sustainable consumption practice and the existence of value-action gap in sustainable consumption practices were also examined. This study adopted multi-stage sampling method. The data of this study originated from Intensification of Research in Priority Areas (IRPA) project conducted in 2004. For the purpose of this study, 289 respondents from Kedah and Perak were selected.The analysis of descriptive statistics and multiple regression were conducted to measure the variables (gender, age, educational level, job category, income level, value towards environment, attitude towards sustainable consumption practices, and materialistic value orientation) and determine the predictors of sustainable consumption practices. The study found that respondents reported high level of value towards environment and attitude towards sustainable consumption practices. The results of descriptive statistics for materialistic value orientation and sustainable consumption practices showed a moderate adoption. Importantly, the analysis on the intensity of adoption revealed that only half of the respondents reported applying sustainable consumption practices (47.8%). The analysis of multiple regression showed that the beta value (B) for value towards the environment is 0.220, attitude towards sustainable consumption practices is 0.265, and materialistic value orientation is -0.203. All psychosocial variables (value towards environment, attitude towards sustainable consumption practices, and materialistic value orientation) have proved to influence sustainable consumption practices. However, none of the socio-demographic variables (gender, age, educational level, job category, and income level) is significant in predicting sustainable consumption practices. Multiple regression analysis revealed that value towards the environment, attitude towards sustainable consumption practices, and materialistic value orientation explained 15% of the variability of sustainable consumption practices. The RSquare value (.15) illustrates a small relationship between the independent and dependent variables. Thus, this demonstrates that there is a value-action gap as the contribution of value and attitude is not strong enough to predict sustainable consumption practices. It also implies that the aspect of practice has to be strengthened. Some strategies involving the aspect of facilities, laws, incentives, and taxes need to be planned. The barriers which might restrain people from applying sustainable consumption practices need to be removed. The campaigns should focus more on the process of consumption and how consumption leads to environmental deterioration. Thus, civil servants in Kedah and Perak have to be awakened that they are a part of something bigger and their consumption practice will make a substantial difference to the earth.